Mengembalikan Peran Kapital Budaya dalam Pendidikan Kritis Berdasarkan Pemikiran Pierre Bourdieu - Norbertus Alexandro Tutu Sare; Adelstein Kadola; Rodriques Payung; Emanuel Gobang (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2026)
Education often serves as a pathway that mobilizes society but simultaneously reproduces social inequality due to the marginalization of cultural capital. As a result, education fails to fulfill its mission of developing critical, moral, and civilized human beings. This qualitative study aims to explore Pierre Bourdieu’s concept of cultural capital and analyze how the dominance of economic and social capital within the education system contributes to the marginalization of cultural capital. The method used is a literature study examining Bourdieu’s theoretical framework. The findings indicate the necessity of repositioning cultural capital to restore the function of education as a space for intellectual and moral empowerment. The dominance of economic and social capital has led education to become pragmatically oriented, reinforcing the reproduction of unjust social structures. Repositioning cultural capital provides a foundation for developing educational policies that strengthen knowledge accessibility, critical literacy, appreciation of arts and culture, and equitable intellectual skills development. Strengthening cultural capital allows education to once again fulfill its essential role as a means of shaping critical, moral, and civilized human beings.AbstrakPendidikan sering menjadi jalan memobilisasi masyarakat yang memproduksi ketimpangan sosial akibat terpinggirkannya kapital budaya. Akibatnya, pendidikan gagal mewujudkan tugas untuk mengembangkan manusia yang kritis, bermoral, dan beradab . Penelitian kualitatif ini bertujuan untuk mengeksplorasi konsep kapital budaya Pierre Bourdieu dan menganalisis bagaimana dominasi kapital ekonomi dan sosial dalam sistem pendidikan berkontribusi terhadap marginalisasi kapital budaya. Metode yang digunakan adalah studi pustaka dengan menelaah pemikiran Bourdieu. Hasil penelitian ini menunjukkan perlunya reposisi kapital budaya untuk mengembalikan fungsi pendidikan sebagai ruang pemberdayaan intelektual dan moral. Dominasi kapital ekonomi dan sosial menjadikan pendidikan cenderung berorientasi pada tujuan pragmatis yang memperkuat reproduksi struktur sosial yang tidak adil. Reposisi kapital budaya menjadi dasar pengembangan kebijakan pendidikan yang menguatkan aksesibilitas pengetahuan, penguatan literasi kritis, apresiasi seni dan budaya, serta pengembangan keterampilan intelektual yang merata. Pengembangan kapital budaya menjadikan pendidikan dapat kembali menjalankan fungsinya sebagai sarana pembentukan manusia yang kritis, bermoral, dan beradab.